Corak Representasi Identitas Ustadz dalam Proses Transmisi Pendidikan Karakter di Pesantren - Mundiri , Akmal; Zahra, Irma (Jurnal Pendidikan Islam Indonesia, 2017)
Pesantren is as educational institution has Tafaqquh fi Al-din- oriented has been long known as an educational Institution whose main purpose form of moral. In the process of transmission can’t be denied the role of ustadz in learning process, both in side and outside classroom. The process of transformation and modernization are all lines require the figure of ustadz in Pesantren to make accommodation, concessions for the transformation of education and learning system in pesantren. Pesantren is as part of the nation's community and also inseparable from the influences of ongoing National dynamics today. It is caught in a wave of globalization with all its positive and negative values. Similarly, ustadz of pesantren which also certainly, cannot be separated from the transformation so that there is a shift in identity representation in the form of mental or language representation. Based on the results of the research was found the figure of ustadz in the framework of accommodation and concessions transformed the representation of identity both as the teacher represented in school such as personality competence competition, social, professional competence, organizational culture skills, both in oral, written form, and personal branding abilities.